Neuroscience and Feminist Political Theory. The Instability Sex-Gender-Sexuality Through the Work of Paul B. Preciado - Medina-Vicent, María (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
Today news about neuroscience is received with great enthusiasm by the general public as well as the academic field. The authority awarded to the results of neuroscientific experiments, linked to its successful dissemination through the mass media, serves to extend the sexual dimorphism argument, opening old feminist debates. Consequently, from a feminist position, we ought to critically approach the neurogenderings and the neurosexism. This aim is performed in order to identify the risks that such discourse entails for feminist political struggle. In order to achieve our objective, we rely on the analysis of the seminal works of feminism, as well as the post-feminist proposal of Paul B. Preciado.
Keywords: neuroscience; neurogenderings; neurosexism; neurofeminism; feminist ethics.